If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(13 + -3a) = -25 (13 * 5 + -3a * 5) = -25 (65 + -15a) = -25 Solving 65 + -15a = -25 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-65' to each side of the equation. 65 + -65 + -15a = -25 + -65 Combine like terms: 65 + -65 = 0 0 + -15a = -25 + -65 -15a = -25 + -65 Combine like terms: -25 + -65 = -90 -15a = -90 Divide each side by '-15'. a = 6 Simplifying a = 6
| 6x+4x+4+8=7x+3+2x | | 4x+5+2x=31 | | -44=-8(-2x+4) | | 4x+2y-3z+a=14 | | -94=8r+3(6-8r) | | (2j+3)-4j-(j+3)= | | 2x-3y+z+5a=-9 | | 2x^2-3px-p=0 | | 3x+15=17+x | | 330=-6(1-7x) | | sinx=0.359 | | 2x(2y-11)=80 | | x+5y=3y-2 | | 2n-8(1+3n)=-96 | | -137=-4(1+8m)-5 | | -137=-4(1+8m) | | 17x-3=3x | | 4x+32=-48 | | 84=-4(3+8x) | | 170=-5(1-7n) | | -5(6+2r)-3r=-108 | | 3m=m+10 | | 464=4k-8(8k+2) | | 200=8(1+8n) | | 136=-3(1-7x)-8 | | h(x)=-16x^2+32x+4 | | 85=-6(k-6)-k | | 1x+3y=7.25 | | 6(-8+3a)=-102 | | 154=7(1-3b) | | -91=-7(x+5) | | 5(-3n+5)-3n=-101 |